Construction of the equations of state for polycrystalline solids for the purpose of the numerical solution of problems of continuous medium mechanics - Ostrik, A V; Nikolaev, D N (Journal of physics. Conference series, 2019)
The equations of state for polycrystalline solids which are in region of compression are developed on experimentally defined shock Hugoniot adiabat and dependence of specific heat on density and temperature. These equations are convenient for the numerical solution of problems of continuous medium mechanics. The numerical method for definition of specific cold energy and the Gruneizen function at T = 0 K depending on compression ratio is proposed. Results of comparison for temperatures behind shock wave in sapphire by means of the developed equations of state and other methods are given.